2015
DOI: 10.1159/000430915
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Combinatorial Pharmacogenomics-Guided Antidepressant Therapy: Evidence from Three Clinical Studies

Abstract: DNA of 258 patients with treatment-resistant depression was collected in three 8-10 week, two-arm, prospective clinical trials. Forty-four allelic variations were measured in genes for the cytochrome P450 (CYP) enzymes CYP2D6, CYPC19, and CYP1A2, the serotonin transporter (SLC6A4), and the 5-HT2A receptor (HTR2A). The combinatorial pharmacogenomic (CPGx™) GeneSight test results were provided to clinicians to support medication changes from baseline (guided arm), or they were provided at the end of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…These comments may be based on analysis of a single gene at a time or in combination. The interpretative report might include comments on a single medication, multiple medications, or a disease‐specific set of medications (e.g., cardiology panel) . Disease‐specific medication set reports may not cover the complete clinical importance of the results if the results applied to medications in multiple clinical areas.…”
Section: Reporting Of Resultsmentioning
confidence: 99%
“…These comments may be based on analysis of a single gene at a time or in combination. The interpretative report might include comments on a single medication, multiple medications, or a disease‐specific set of medications (e.g., cardiology panel) . Disease‐specific medication set reports may not cover the complete clinical importance of the results if the results applied to medications in multiple clinical areas.…”
Section: Reporting Of Resultsmentioning
confidence: 99%
“…Multiple studies have recently been published illustrating the clinical value of multigene pharmacogenetic panels when treating patients with depression. At least four rigorous studies have shown significantly better treatment outcomes for major depressive disorder with pharmacogenomic guidance compared with the standard clinical approach .…”
Section: Antidepressant Selectionmentioning
confidence: 99%
“…For example, it is unclear whether these pharmacogeneticguided tools can shorten the time to remission and/or sustain the duration of remission from depression. Furthermore, the utility of these tools for assisting in the decision to switch or augment a patient's current prescription remains uncertain, although preliminary evidence suggests these tools may assist with medication changes [33]. Finally, the cost-effectiveness of pharmacogenetic decision support tools remains unclear [34] and until robust economic studies are conduced, firm clinical guidelines or recommendations cannot be made.…”
Section: Evidence-base For Pharmacogenetic Decision Support Toolsmentioning
confidence: 99%